Effects of different metabolizable energy levels on apparent nutrient digestibility and metabolism, blood biochemical indicators, and fecal flora diversity in racing pigeons undergoing exercise training - Li, Xiao bin; Guo, Xin sheng; Li, Hai ying; Liu, Jia jia; Lin, Jian wei; Zheng, Sheng chen; Ke, Li feng (Frontiers in Microbiology, 2025)
This study aimed to determine the optimal dietary energy requirements for pigeons undergoing exercise training. A total of 200 pigeons were randomly assigned to five groups (n = 40 per treatment) and subjected to 1 h of daily flight training. A one-way ANOVA design was employed, testing five dietary energy levels (12.03, 12.20, 12.32, 12.46, and 12.59 MJ/kg). The experiment lasted for 90 days. Results indicated that the metabolizable energy (ME) level significantly influenced nutrient digestion and metabolism, serum biochemical variables, and the microbial diversity and composition of exercise-trained pigeons. Specifically, the T5 group (12.59 MJ/kg) showed a significant increase in apparent organic matter (OM) digestion (P < 0.05), while the T4 group (12.46 MJ/kg) exhibited a significant increase in crude protein (CP) digestion (P < 0.01). Both the T2 and T5 groups demonstrated increased crude fat (EE) digestion (P < 0.05). Biochemical analysis revealed that the total protein (TP) and globulin (GLB) levels in the T1 group were significantly higher (P < 0.05 or P < 0.01). The T4 group showed elevated aspartate aminotransferase (AST) and alanine aminotransferase (ALB) levels (P < 0.05), while the T2 group exhibited significantly increased triglycerides (TG) and glucose (GLU) levels (P < 0.05 or P < 0.01). The T5 group had significantly higher catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GSH-PX), and total antioxidant capacity (T-AOC; P < 0.05 or P < 0.01), whereas malondialdehyde (MDA) levels were significantly reduced (P < 0.01). Additionally, dietary ME levels affected microbial diversity and composition. The T1 group had higher abundance of Halobacterota and Verrucomicrobiota compared to the other groups (P < 0.05), while Lactobacillus abundance was greater in the T1 group than in the T3 group (P < 0.05). In contrast, Clostridium_sensu_stricto_1 and Romboutsia were more abundant in the T3 group compared to the T1, T2, T4, and T5 groups (P < 0.05). The T5 group exhibited higher abundance of Ligilactobacillus than the T1 and T2 groups (P < 0.05). Correlation analysis revealed a significant positive relationship between MDA and Halobacterota, Halobacteria, Bacillales, Bacillaceae, Moraxellaceae, and Bacillus (P < 0.05). CAT was positively correlated with DNA metabolism, replication and repair, and nucleotide metabolism (P < 0.01), while T-AOC was positively associated with food synthesis, replication and repair, and glycan biosynthesis and metabolism (P < 0.05). GSH-PX was positively correlated with membrane transport, replication and repair, and nucleotide metabolism. MDA also showed a significant positive correlation with signal transduction (P < 0.05). In conclusion, the study indicates that ME levels ranging from 12.03 to 12.59 MJ/kg significantly influence nutrient digestion, metabolism, serum biochemistry, and microbial diversity in exercise-trained pigeons. For optimal nutrient requirements, health, gastrointestinal balance, and economic efficiency, a dietary ME level of 12.32–12.46 MJ/kg is recommended for practical pigeon production.